Evaluation Analysis of the Implementation of the Puskesmas Management Cycle in the Health Office of the South Sorong District in 2024 - Ruhwandi, Ruhwandi; Adam, Arlin; Iskandar, Ishaq; Zamli, Zamli (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Management of puskesmas is critical to providing quality health services through effective planning, organising, implementing, and controlling. Improving the quality of health services builds patient trust. The Healthy Indonesia Programme aims to improve services at first level health facilities, including puskesmas, but many still do not meet quality standards. This study evaluates the management cycle of puskesmas at the South Sorong District health office.Objectives: This study aims to analyse the evaluation of the implementation of the puskesmas management cycle at the South Sorong District Health Office. Methods: A qualitative approach was used with informants from four puskesmas: Teminabuan, Konda, Kokoda, and Kais Darat, representing 16 puskesmas in the region.Results: Some puskesmas follow the planning stages involving mini-workshops and Introspection Survey data, but not consistently. There were challenges maintaining the monthly mini-workshop schedule and using the monthly work programme plan results. Monitoring processes were not always optimal, with most responsibility falling on the head of the puskesmas and administrative staff, while the role of the programme focal point was not fully maximised.Conclusion: puskesmas should improve the consistency, quality, and effectiveness of management through increased managerial competence, efficient budget management, and optimisation of planning, implementation, and monitoring processes.